Diallel analysis for yield and yield contributing characters in Indian mustard (Brassica juncea) (Journal of Oilseed Brassica, 2026)
Diallel analysis in mustard involving ten parents and forty five crosses was performed to estimate the general (gca) and specific combining ability (sca) of parents and crosses respectively. The gca and sca effects showed wide variation in the level of significance for various yield contributing characters. The parents Seeta, Varuna and Laxmi were identified as best general combiners for yield and yield contributing characters on the basis of high mean performance and significant gca effects. Among the crosses Varuna x Seeta was identified as best F1 cross, which can be forwarded to the next generation by single seed descent method with an aim of getting useful segregants in the succeeding generation